Hormonal and inflammatory modulatory effects of hesperidin in hyperthyroidism-modeled rats - Ashry, Mahmoud; Askar, Hussam; Obiedallah, Manar M.; Elankily, Ahmed Hussuin; Galal El-Sahra, Doaa; Zayed, Gamal; Mustafa, Mohamed A.; El-Shamy, Sawsan Abd El-Maksoud; Negm, Somaia A.; El-Beltagy, Marwa A.; Abdel-Wahhab, Khaled G.; Ene, Antoaneta (Frontiers in Immunology, 2023)
The goal of the current study was to investigate the hormonal modulatory efficiency of hesperidin, through its regulatory potential of immunological, inflammatory, and/or antioxidant changes in on hyperthyroidism modeled adult female albino rats. Both normal and hyperthyroidism modeled rats (140-160g) were randomly divided into four groups (10 animals each) as follows: 1) healthy animals were daily ingested with saline for six weeks, and served as control group, 2) healthy animals were intraperitoneally injected with hesperidin (50 mg/kg/day) for a similar period, 3) hyperthyroidism-modeled animals without any treatment acted as positive control, and 4) hyperthyroidism-modeled animals were treated intraperitoneally with hesperidin for a similar period. The findings showed that hesperidin significantly modulated hyperthyroidism deteriorations, this was evidenced by a remarkable decline in serum T4, FT4, T3, FT3, TNF-α, IL1β-, IL4-, IL-6, and IL-10 levels, with a minor increase in TSH and significant raise in CD4+ level. Similarly, valuable improvement was observed in the oxidative status; serum SOD, GPx, CAT, and GSH levels were dramatically enhanced, associated with remarkable drop in MDA and NO levels. Also, hesperidin demonstrated nephro-hepatoprotective and anti-atherogenic potential, this was achieved from the notable reduction in ALAT and ASAT activities as well as urea, creatinine, cholesterol, and triglyceride close to the corresponding values of healthy group. These findings were supported by histological and immunohistochemical ones that showed a notable decrease in the expression of the calcitonin antibody. In conclusion, hesperidin possesses anti-hyperthyroidism, immunoinflammatory regulatory, and antioxidant activities that evidenced from the improvement of physio-architecture of the thyroid gland, reduction of inflammation and restoration of the impaired oxidative stress. This effect might be mechanized through immunological, inflammatory, apoptotic, and/or antioxidant modulatory pathways.